Ethnomedicinal claims of some botanicals sold by vendors in North Maharashtra (India) - Patil2, Y. A. Ahirrao1*, Patil M.V.1 and D. A. (Journal of Ecobiotechnology, 2011)
Ethnobotanical surveys were carried out since June 2008 and information was gained through open discussions and interviews with the tradipractitioners. The present paper deals with the botanicals sold by the vendors in Nasik, Dhule, Nandurbar, Jalgaon and Buldhana districts of North Maharashtra (India). The objective of investigation was to gather and document information on application of botanicals by the tradipractitioners in the region. Presently, 29 plant species belonging to 29 genera and 24 families are being informed. Of these, 21 species are noted for the first time from Indian region. The data accrued is evaluated by cross-cultural comparisons with other Indian claims to bring out veracity and additional claims. These are administered in the form of decoction, infusion, paste, oil, juice, powder, extract, etc.Ã‚Â  In many applications, they use a sole drug or occasionally supplemented by other botanicals or substances like sugar, honey, oil, cow-ghee, cow, goat-milk, etc. These are administered to combat common diseases such as snake-bite, sperm count, diabetes, sun stroke, eczema, bleeding, body heat, heart problem, rheumatism, stomach complaints, migraine, ulcer, asthma, abdominal pain, whiteness of eyes, sexual power, tooth-ache, menstruation, impotency, leucorrhoea, bone fracture, piles, jaundice, heart attack, etc.